Finance and inequality in West African countries: does size matter? - Yusuf, Muhammad-Bashir Owolabi; Mahadi, Nur Farhah (Sciendo, 2024)
This study delves into the intricate interplay between finance and income inequality within the context of 16 West African nations. It specifically scrutinizes the impact of the size of financial development on income inequality, drawing inspiration from Greenwood and Jovanovic's (1990) theory. The analysis spans a substantial period, from 2010 to 2020, and relies on panel secondary data. A comprehensive examination of the data employs various estimation techniques, including Pooled Ordinary Least Square, Random Effect Model, Fixed Effect Model, and the Generalized Method of Moments (GMM), to elucidate the relationship under investigation. The panel data analysis results strongly favor the Fixed Effect model. Furthermore, both the Fixed Effect model and the GMM reveal substantial support for an inverted U-shaped relationship, demonstrating remarkable robustness with slight variations in significance. Notably, the study highlights the significance of lagged Gini values, GDP per capita growth, trade openness, inflation, government consumption, and infrastructure in influencing income inequality